Food and nutrition (in)security in times of pandemic COVID-19: challenges and hunger (Research, Society and Development, 2022)
Objective: to evaluate recent scientific evidence about food and nutritional insecurity in pandemic´s time  and its effects and challenges related to hunger. Methodology:  a review   of the literature´s narrative based on bibliographic searches of articles in Portuguese, English and Spanish, available in PubMed, Scielo and Lilacs. For the development of the study, the searches were carried out in the period from March 2021 to May 2022, the choice of this period met the criterion of temporality, in which the cut of two years was considered, as these are more current publications, Articles available in full were included. The descriptors used to build the study and research were: “Food insecurity”, “Food security”, “Pandemic” and “COVID-19”. Results: Poverty and inequality are the structural and underlying causes of all forms of (AI) and malnutrition, amplifying the negative impact of global factors, thus, in the context of the pandemic, AI is directly linked to undeniable poverty population, making society a frontline for challenges beyond the health crisis. Income inequality, in particular, increases the likelihood of AI especially for socially excluded and marginalized groups and reduces the positive impact of any economic growth on individual food security. Therefore, transforming food systems is critical to achieving food security, improving nutrition and making healthy eating accessible to all. Final considerations: measures to eradicate hunger, food insecurity and protect lives require a clear joint effort and participatory societal responsibilities, especially in the development of plans and strategies, and accountability of governments in maintaining revenues, realizing rights, investments and policies public.